The flag and the cross white Christian nationalism and the threat to American democracy - Gorski, Philip S. 1963-; Perry, Samuel L. (Oxford University Press, 2022)
In this short primer, Gorski and Perry explain what white Christian nationalism is and is not; when it first emerged and how it has changed; where it's headed and why it threatens democracy. Tracing the development of this ideology over the course of three centuries and especially its influence over the last three decades, they show how white Christian nationalism motivates the anti-democratic, authoritarian, and violent impulses on display in our current political moment
Keywords: Demokratie; Christ; Nationalismus; USA; Christianity and politics / United States / History / 21st century; Nationalism / United States / Religious aspects / History; Christians, White / United States / History / 21st century; Christianity and culture / United States / History; Christianity / Influence; Christianisme et politique / États-Unis / Histoire / 21e siècle; Christianisme et civilisation / États-Unis / Histoire; Christianisme / Influence; Nationalisme / États-Unis / Aspect religieux / Histoire; Christianity and culture; Christianity and politics; Christians, White; Nationalism / Religious aspects; United States; 2000-2099; History